Active tectonics, paleoseismology and seismic hazards of the piedmont Xizhoushan fault zone in the Shanxi graben system, North China Block. (January 2021) - ZhongyuanYu,; Yin, Na; Wang, Chengyang; Deng, Miao; Lan, Weiguang
Graphical abstract: Highlights: The Xizhoushan Fault Zone experienced intensive paleoseismicity in late Quaternary. The co-seismic surface rupture of 1038 CE 7¼ Dingxiang earthquake may be ~60 km long. The present tectonic deformation of the Xizhoushan Fault changes into normal dextral. Abstract: Major active strike-slip fault zones in graben systems play an important role in releasing the strain energy. In this study, the active tectonics, paleoseismicity and seismic hazards of the Xizhoushan Fault Zone (XFZ) in the Shanxi graben system, North China Block (NCB), are examined through high-resolution satellite image interpretations, field investigations, outcrop and trench excavations, and dating of geochronology samples. Modern alluvial terraces of gullies and loess accumulations are systematically deflected and/or offset with co-seismic collapse, landslides and scarps, indicating that the XFZ has been active in the late Quaternary and is characterized by normal dextral strike-slip movements. The late Holocene slip rate of the XFZ is estimated to be ~2.0 ± 0.2 mm/yr in the horizontal and 0.5 ± 0.10 mm/yr in the vertical. Field observations reveal that at least three morphogenic earthquakes occurred on the XFZ in the Holocene, hinting at an average recurrence interval of ~3000 yrs. The latest event occurred at ~1.50 ± 0.6 ka BP and very likely corresponds to the 1038 CE Dingxiang M 7¼ event. The penultimate event occurred at ~4.10 ± 1.60 ka BP, and the antepenultimate event is inferred to have occurred between ~13.17 ± 1.43 ka BP and ~8.29 ± 0.90 ka BP. Our studies suggest that the strain energy accumulating along the XFZ is released by repeated strike-slip displacements of the modern stream channels, alluvial terraces and loess accumulations, while the earthquake potential (M ≥ 7) is low in the short term. The research also hints that the present dextral slip along NNE-trending faults has replaced the once predominately extensional deformation in the NCB.